2020
DOI: 10.1111/srt.12970
|View full text |Cite
|
Sign up to set email alerts
|

Using laser Doppler flowmetry with wavelet analysis to study skin blood flow regulations after cupping therapy

Abstract: Background The purpose of this study was to use laser Doppler flowmetry (LDF) with wavelet analysis to investigate skin blood flow control mechanisms in response to various intensities of cupping therapy. To the best of our knowledge, this is the first study to assess skin blood flow control mechanism in response to cupping therapy using wavelet analysis of laser Doppler blood flow oscillations. Materials and Methods Twelve healthy participants were recruited for this repeated‐measures study. Three different i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
0
27
0
1
Order By: Relevance
“…In this study, a significant delayed effect, but not an immediate effect, of cupping therapy on reducing muscle fatigue may be related to the differences in removal speed of intramuscular hydrogen ions (H + ) after cupping therapy ( Sahlin et al, 1998 ). Cupping therapy can increase blood flow ( Hou et al, 2020 ), which may increase clearance of H + . The high [H + ] within the muscle produced by biceps curls could restrain the sarcoplasmic reticulum from releasing Ca 2+ into sarcoplasm, and inhibit the binding of Ca 2+ to troponin through the competitive binding of H + to Ca 2+ -specific sites on troponin C ( Sahlin, 1992 ; Fitts, 1994 ) and it could reduce myofibrillar ATPase activity ( Metzger and Moss, 1987 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, a significant delayed effect, but not an immediate effect, of cupping therapy on reducing muscle fatigue may be related to the differences in removal speed of intramuscular hydrogen ions (H + ) after cupping therapy ( Sahlin et al, 1998 ). Cupping therapy can increase blood flow ( Hou et al, 2020 ), which may increase clearance of H + . The high [H + ] within the muscle produced by biceps curls could restrain the sarcoplasmic reticulum from releasing Ca 2+ into sarcoplasm, and inhibit the binding of Ca 2+ to troponin through the competitive binding of H + to Ca 2+ -specific sites on troponin C ( Sahlin, 1992 ; Fitts, 1994 ) and it could reduce myofibrillar ATPase activity ( Metzger and Moss, 1987 ).…”
Section: Discussionmentioning
confidence: 99%
“…We chose 5 min for the duration of cupping therapy because previous studies have used durations ranging from 5 to 20 min for different impairments ( Sanders et al, 1995 ; Tham et al, 2006 ; Dayer-Berenson, 2010 ; Roostayi et al, 2016 ). Our previous studies demonstrated that cupping therapy at –300 mmHg for 5 min could significantly increase skin blood flow of the upper arm ( Hou et al, 2020 ). Thus, we used cupping therapy at –300 mmHg for 5 min to reduce muscle fatigue in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is no consensus about the potential mechanisms of cupping therapy, a local increase in blood flow is mostly accepted as a critical factor (Sloas et al, 2016;Lowe, 2017;Hou et al, 2020). After the removal of cup, cupping therapy causes an increase in local blood flow and lymphatic flow that may be helpful for relieving myofascial pain and improving soft tissue healing (Jafri, 2014;Sloas et al, 2016;Lowe, 2017).…”
Section: Introductionmentioning
confidence: 99%